Consumo sustentável e ambiente : o papel do Estado e das políticas públicas na inculcação de disposições ambientalistas - Cruz, Isabel Silva (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2016)
The harmful effects of consumption on the environment brought to the political agenda issues of sustainable consumption. In this article we propose to perform a retrospective analysis of the centrality that the issues of sustainable consumption and the environment assumed for the several Portuguese governments from 1976 to 2015. Grounded in the theoretical perspectives of ‘growth’ and ‘degrowth’ and its relationship with the concept of sustainable consumption using the documentary analysis, we discuss both the relationship between the environment and the economy, and likewise the effectiveness of strategies privileged by different constitutional governments in order to inculcate environmental dispositions.